2018
DOI: 10.18632/oncotarget.25891
|View full text |Cite
|
Sign up to set email alerts
|

3D hydrogel breast cancer models for studying the effects of hypoxia on epithelial to mesenchymal transition

Abstract: Solid tumors are 3D assemblies of cancer cells, together with multiple stromal cell types within an extracellular matrix. Yet, the vast majority of cell-based studies to characterize oncogenesis and discovery of new anti-cancer drugs is conducted using conventional 2D monolayer culture systems, where cells are grown on plastic substratum under normoxic environments. In current study, we generated 3D breast cancer cell culture platform consists of photocrosslinkable hydrogels and encapsulated isogenic primary (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 66 publications
1
29
0
3
Order By: Relevance
“…In this review a total of 51 publications [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ] utilized various levels of external hypoxia control, primarily through control of the atmospheric oxygen level of the chamber. The remaining studies validated hypoxia through a number of different routes including; internally generated hypoxia within cultures through the use of pO 2 probes to measure the m...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this review a total of 51 publications [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ] utilized various levels of external hypoxia control, primarily through control of the atmospheric oxygen level of the chamber. The remaining studies validated hypoxia through a number of different routes including; internally generated hypoxia within cultures through the use of pO 2 probes to measure the m...…”
Section: Resultsmentioning
confidence: 99%
“…EMT is a process identified as one of the key features in tumour invasion and metastasis. We identified a total of 19 publications [ 15 , 24 , 50 , 69 , 73 , 74 , 76 , 82 , 84 , 92 , 94 , 99 , 100 , 101 , 102 , 104 , 105 , 106 , 107 ] comparing markers of EMT in 2D vs. 3D tumour cultures, with 18 of those showing enhanced measurements of EMT in 3D compared to 2D cultures. In contrast with the generalised cohort of studies concerning biomimicry of in vitro cancer cultures, the studies specifically concerning EMT consisted of a majority of scaffold-based cultures at 67%, and 33% involving non-scaffold-based cultures.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that gene expression in 3D cell cultures better resemble clinical expression profiles than their 2D counterpart [25]. Like solid tumors in patients, their 3D architecture creates a gradient of nutrients and oxygen that ultimately affects expression of important genes associated with drug response, leading to an increase in resistance to some compounds [26,27]. Hence, 3D cell cultures can be used as a tool to test whether the biological effects observed in a 2D setting are maintained in a more complex 3D architecture [28].…”
Section: Discussionmentioning
confidence: 99%
“…[11] This ushers in the importance of 3D in vitro culture systems in dissecting and studying the various hallmarks of cancer. [8] Various kinds of 3D models, such as hydrogel constructs, [12] polymeric scaffolds, [13,14] microcarrier beads, [15] and hanging droplets [16] have been increasingly used in studying different aspects of tumor growth. Such 3D models preserve the cell-cell and cell-matrix interactions that dictate the entire metastatic cascade, including formation of primary neoplasm, initiation of tumor vasculature, tumor cell invasion into the surrounding matrix, and intravasation into surrounding blood vessels to eventually form secondary malignancies.…”
mentioning
confidence: 99%